2017
DOI: 10.1177/0038040717710494
|View full text |Cite
|
Sign up to set email alerts
|

School Choice, Gentrification, and the Variable Significance of Racial Stratification in Urban Neighborhoods

Abstract: Racial and socioeconomic stratification have long governed patterns of residential sorting in the American metropolis. However, recent expansions of school choice policies that allow parents to select schools outside their neighborhood raise questions as to whether this weakening of the neighborhood–school connection might influence the residential decisions of higher-socioeconomic-status white households looking to relocate to central city neighborhoods. This study examines whether and the extent to which exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 54 publications
7
96
0
1
Order By: Relevance
“…Some parents may feel more comfortable residing in gentrifying neighborhoods precisely because there are non-neighborhood school options available. Indeed, one recent study found that gentrification is more likely to occur in minority neighborhoods with non-neighborhood school options (Pearman and Swain 2017). Public choice options such as magnet schools, originally created to attract higher-SES families, offer special programs and curriculums (e.g., language immersion and arts programs) that may appeal to middle-class parents seeking non-neighborhood alternatives (Jordan and Gallagher 2015).…”
Section: Examining Dynamics In Gentrifying Neighborhoodsmentioning
confidence: 99%
“…Some parents may feel more comfortable residing in gentrifying neighborhoods precisely because there are non-neighborhood school options available. Indeed, one recent study found that gentrification is more likely to occur in minority neighborhoods with non-neighborhood school options (Pearman and Swain 2017). Public choice options such as magnet schools, originally created to attract higher-SES families, offer special programs and curriculums (e.g., language immersion and arts programs) that may appeal to middle-class parents seeking non-neighborhood alternatives (Jordan and Gallagher 2015).…”
Section: Examining Dynamics In Gentrifying Neighborhoodsmentioning
confidence: 99%
“…In addition, school choice might exacerbate gentrification by separating school contexts from neighborhoods (Billings et al. ; Pearman and Swain ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agencies also bring better financing options to gentrifying neighborhoods, which works in conjunction with other revisions such as better city services (Moskowitz 2017). In addition, gentrifying locations benefit from urban charter schools, which attract households with children (Pearman and Swain 2017). Rising home prices and taxes in gentrifying locations limit access to these places.…”
Section: Organizational Activity Environment As a Context Of Categorimentioning
confidence: 99%